2007
DOI: 10.1186/1744-9081-3-34
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine receptor polymorphisms with schizophrenia and antipsychotic response in a South Indian population

Abstract: Background: Alterations in the dopamine transmission and receptor density are hypothesized in the pathophysiology of schizophrenia but ethnic disparities are reported to exist in disease association and therapeutic response to psychotropic medication. Antipsychotics have higher binding affinity to D2 subtype of dopamine receptor. DRD2 Cys311, TaqIB1 and TaqIA1 variants are considered to have either reduced affinity for dopamine and hypo-dopaminergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 52 publications
(49 reference statements)
3
34
0
Order By: Relevance
“…A more recent study of a Caucasian population from the north of Spain reported a lower frequency of the A1 allele in schizophrenic patients than in controls (Parsons et al 2007). The A2 homozygous genotype also appeared to be overrepresented in schizophrenic patients from South India (Vijayan et al 2007). In summary, the A2 allele of TaqIA appears to be predominant in different samples of patients with schizophrenia.…”
Section: Schizophreniamentioning
confidence: 93%
“…A more recent study of a Caucasian population from the north of Spain reported a lower frequency of the A1 allele in schizophrenic patients than in controls (Parsons et al 2007). The A2 homozygous genotype also appeared to be overrepresented in schizophrenic patients from South India (Vijayan et al 2007). In summary, the A2 allele of TaqIA appears to be predominant in different samples of patients with schizophrenia.…”
Section: Schizophreniamentioning
confidence: 93%
“…For example, several studies found no association with schizophrenia in an Indian population for several polymorphisms, such as RS12808482, RS11608185, and the Taq1D (Caprini, et al, 2011;, although one earlier study had found a moderate association between the Taq1D genotype and treatment success in schizophrenia (Vijayan, et al, 2007). One study revealed no link for the Taq1D SNP with reward sensitivity in binge eating disorders (Davis, et al, 2008), another found no link with sensation-seeking for any of 40 SNPs in the DRD2 gene (Derringer, et al, 2010), and still another found no link with ADHD symptomatology among ADHD children and their families (Kollins, et al, 2008).…”
Section: Snp Proxy Search For Rs1116313 Snpmentioning
confidence: 99%
“…Pharmacogenomics: With increasing interest in the role of genetic factors in the treatment response and side effects of medications, studies from India have tried to address the genetic links of tardive dyskinesia, treatment response and severity of psychopathology (Tiwari et al 2005;Vijayan et al 2007;Thomas et al 2008;Gupta et al 2009Gupta et al , 2013. However, the findings are preliminary and inconclusive.…”
mentioning
confidence: 98%
“…Tiwari et al (2005) evaluated the role of six single nucleotide polymorphisms (SNP) in tardive dyskinesia and showed that CYP1A2 1545 C > T SNP was associated with tardive dyskinesia and schizophrenia, but the association was rendered insignificant after corrections for multiple comparisons. Vijayan et al (2007) studied various alleles, genotypes, haplotypes and their linkage disequilibrium and observed that H313HTT genotype was associated with schizophrenia and TaqIB1B1 genotype was significantly associated with higher psychopathology scores. Subjects with H313HCC, TaqIA2A2 and Taq1D1D1 had higher mean improvement scores.…”
mentioning
confidence: 99%